PSXII-25 The Effects of Poor Maternal Nutrition on Fetal Brain Development. (7th December 2018) - Engels, L; Wynn, M; Smith, B; Hoffman, M; Jones, A; Pillai, S; Reed, S; Zinn, S; Duan, J; Tian, X; Govoni, K
Abstract: Poor maternal nutrition affects the development and growth of a variety of tissues and organs in offspring. However, research on the effects of poor maternal nutrition on offspring brain development is limited. There is evidence that fetal brain is influenced by maternal diet in the last third of gestation, where brain growth is at its peak. Therefore, we hypothesized that maternal restricted- and over-feeding during gestation would decrease the expression of genes involved in offspring brain development. To investigate, pregnant Western White-faced ewes ( n = 16) were individually housed and fed a control- (100% NRC), restricted- (60% NRC), or over-fed (140% NRC) diet starting at d 30.2 ± 0.2 of gestation. At d 135 of gestation, ewes and fetuses ( n = 6 control, 12 restricted, and 9 over) were euthanized and brain tissue collected from offspring. Samples were snap frozen and stored at -80°C. Brain tissue RNA was extracted using a Qiagen RNeasy kit, reverse transcribed, and real-time PCR was performed. The mRNA expression of three genes involved in brain development and neurogenesis was quantified, including Brain Derived Neurotrophic Factor ( BDNF ), Katanin Regulatory Subunit B1 ( KATNB1 ), and Microcephalin ( MCPH1 ). Glyceraldehyde 3-phosphate dehydrogenase was used as the housekeeping gene. Data were analyzed using PROC MIXED in SAS with the main effect as maternal diet. Significance was determined at P ≤ 0.05. No effect of maternal diet on gene expression was observed for BDNF ( P = 0.66), KATNB1 ( P = 0.36), or MCPH1 ( P = 0.36). Lack of changes could be due to age of offspring as others have shown that poor maternal diet affects mRNA expression of genes relating to neurodevelopment postnatally. Additional research is necessary to determine whether poor maternal nutrition affects other genes relating to brain development and cognition in offspring as well as at different time points.